2003
DOI: 10.1007/s00417-003-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of spontaneous eyeblink activity during video display terminal use in healthy volunteers

Abstract: VDT use is associated with a profound decrease of the SEBR in healthy subjects. There are marked interindividual differences in SEBR and no correlation between the SEBR and ocular tear film parameters in normal eyes. The SEBR is further reduced by corneal anaesthesia. The presence of different patterns of eyeblinking may be related to various exogenous and endogenous factors and may lead to a better understanding of ocular reactions during VDT use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 21 publications
11
62
0
3
Order By: Relevance
“…This SEBR is in 8 agreement with previous studies assessing blinking in similar conditions (although in some of 9 these studies viewing distance was not adjusted with a chin and forehead rest) [15,[17][18][19][20][21]. A 10 statistically significant difference in SEBR was encountered between the four reading sessions, 11…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This SEBR is in 8 agreement with previous studies assessing blinking in similar conditions (although in some of 9 these studies viewing distance was not adjusted with a chin and forehead rest) [15,[17][18][19][20][21]. A 10 statistically significant difference in SEBR was encountered between the four reading sessions, 11…”
Section: Resultssupporting
confidence: 81%
“…It may be observed that these studies follow two main strategic approaches to improve SEBR: 8 they either elicit some type of reflex blinking or they aim at influencing the regulation of the 9 central blinking "pacemaker", which has been shown to be highly sensitive to the cognitive 10 demands of the undergoing task [18][19][20][21]. It may be assumed that strategies relying on a 11 sustained contribution of reflex blinking might be graded by participants as more intrusive 12 than those based on subtle modulations of the activity of the internal "pacemaker" [28].…”
Section: Resultsmentioning
confidence: 99%
“…computer screens, computer environments, human eyes, computer users, and computer tasks (18). Blinking plays an important role in maintaining the integrity of the ocular surface, and the occurrence of dry eye symptoms can be associated with decreased blink rate (19). A reduced blinking rate contributes to a poor tear film quality and temporarily stresses the cornea, and may lead in symptoms of dry eye that can be easily managed by applying lubricating eye drops or artificial tears (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, on the one hand, increasing cognitive demands have been reported to result in a reduction in SBR, both during computer tasks [7][8][9][10][11] and other activities such as reading or watching a video story. 4,5 On the other hand, blinks tend to be associated with large gaze shifts, rather than saccades of smaller amplitude such as those involved in reading, 20,21 partially contributing to sustaining visual stability through momentary suppression of visual input, 16,17 which is particularly relevant for large gaze shifts, were saccadic suppression is less effective.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, a similar reduction in blinking frequency with increasing task complexity has been evidenced in relation to computer use, a field in which spontaneous blinking has been extensively studied in order to understand and alleviate the symptomatology associated with the traditionally known as ''computer vision syndrome''. [7][8][9][10][11] Interestingly, from a different perspective, the increased blink rate observed in studies investigating behavioral indicators of fatigue and drowsiness has been related to a cessation of the attention-driven inhibitor of blinks.…”
Section: Q1mentioning
confidence: 99%